The aeolic dialects of ancient Greek : a study in historical dialectology and linguistic classification - Scarborough, Matthew (Brill's studies in Indo-European languages & linguistics,, 2023)
The Aeolic dialects of Ancient Greek (Lesbian, Thessalian, and Boeotian) are characterised by a small bundle of commonly shared innovations, yet at the same time they exhibit remarkable linguistic diversity. While traditionally classified together in modern scholarship since the nineteenth century, in recent decades doubt has been cast on whether they form a coherent dialectal subgroup of Ancient Greek. In this monograph Matthew Scarborough outlines the history of problem of Aeolic classification from antiquity to the present day, exhaustively collects and analyses the primary evidence for the linguistic innovations that unite and divide the group, and contributes an innovative new statistical methodology for evaluating highly contested genetic subgroupings in dialectology, ultimately arguing in support of the traditional classification.